Method for synthesizing hyaluronic acid nanoparticles, and hyaluronic acid nanoparticles prepared by the method

By using electron beam irradiation in acidic hyaluronic acid aqueous solution to form crosslinked hyaluronic acid nanoparticles, the problem of preparing nanoparticles without crosslinking agents is solved, the control of nanoparticle size is achieved, and its application scope is expanded.

CN113825786BActive Publication Date: 2025-02-07KYUNGPOOK NAT UNIV IND ACADEMIC COOP FOUND
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202080015373.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-01-11
Filing Date
2020-01-13
Publication Date
2025-02-07
Estimated Expiration
2040-01-13

AI Technical Summary

Technical Problem

The prior art is difficult to prepare pure hyaluronic acid nanoparticles with biocompatible without crosslinking agents, and the size of the prepared nanoparticles is difficult to control, limiting their application in various fields.

Method used

Hyaluronic acid nanoparticles with a diameter of 1 to 100 nanometers are prepared by irradiating electron beams in an aqueous acid hyaluronic acid solution and by adjusting the irradiation dose and solution pH value to control the size of nanoparticles.

Benefits of technology

The preparation of biocompatible hyaluronic acid nanoparticles without crosslinking agents was achieved, and the size of the nanoparticles was successfully controlled, expanding its application potential in the fields of biomedical and cosmetics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113825786B_ABST
    Figure CN113825786B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing cross-linked hyaluronic acid nanoparticles, which comprises forming intermolecular or intramolecular cross-links of hyaluronic acid by irradiating an aqueous hyaluronic acid solution with an electron beam. Hyaluronic acid nanoparticles having various nanometer sizes can be reproducibly and consistently synthesized under optimized electron beam conditions, and the present invention provides the use of the synthesized hyaluronic acid nanoparticles as a therapeutic agent and as a contrast agent for determining skin permeability by fluorescent labeling and diagnosing tumors by radiolabeling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims the benefit of Korean Patent Application No. 10-2019-0003966, filed on January 11, 2019, which is hereby incorporated by reference in its entirety into this application.

[0002] The present invention relates to a method for preparing pure cross-linked hyaluronic acid nanoparticles with biocompatibility without a cross-linking agent, nanoparticles prepared by the method and applications of the nanoparticles. Background Art

[0003] Hyaluronic acid is a component that makes up skin cells together with elastin and collagen. It is known as a moisturizer that can store 1000ml of water per 1g and has been widely used as a cosmetic material.

[0004] There is a need for in vivo usable and biocompatible nanoparticles such as pure hyaluronic acid hydrated gels for use as contrast agents and in vivo. Research using hyaluronic acid that has been cross-linked and converted to nanoparticle form is in its early stages, and research on synthesizing nanoparticles without the use of cross-linking agents has rarely been reported.

[0005] Meanwhile, a method for preparing nanoparticles by irradiating a hyaluronic acid aqueous solution with an electron beam is provided (Korean Patent Registration No. 10-1893549). However, due to the high concentration of hyaluronic acid under the conditions for preparing nanoparticles, it is not economical and only nanoparticles with a diameter greater than 100 nm can be prepared, so the application in various fields is limited. Summary of the invention

[0006] Technical issues

[0007] Thus, by recognizing conventional problems and needs, the present invention provides a new method for preparing biocompatible pure hyaluronic acid nanoparticles or nanogels.

[0008] The present invention provides a method capable of forming cross-linked hyaluronic acid nanoparticles on an aqueous solution other than an organic solvent without a separate cross-linking agent, and provides a method capable of controlling the size of the nanoparticles.

[0009] Technical Solution

[0010] In one aspect, the present invention provides a method for preparing cross-linked hyaluronic acid nanoparticles, which comprises forming intermolecular or intramolecular cross-links of hyaluronic acid by irradiating an aqueous hyaluronic acid solution with electron beams.

[0011] In the present invention, nanoparticles refer to particles with a size of several nanometers (nm, a material of one billionth of a meter) to several hundred nanometers. In the present invention, nanoparticles are characterized in that their particle diameter is 1 to 100 nanometers, but are not limited thereto. In the present invention, nanoparticles are concepts including nanogels or nanohydrogels, and hereinafter, nanoparticles, nanogels or nanohydrogels are all used to refer to nanoparticles of the present invention.

[0012] The hyaluronic acid aqueous solution is acidic, and for acidic aqueous solutions, HClO4 can also be included in the solution containing hyaluronic acid. As described in detail below and confirmed, when the hyaluronic acid aqueous solution is acidic or acid is added to the hyaluronic acid aqueous solution, it is newly proved that the high nanoparticle synthesis efficiency is increased compared with the hyaluronic acid aqueous solution when it is not acidic or when acid is not added to the hyaluronic acid aqueous solution. The present invention has also proved that the size of the nanoparticles can be unexpectedly controlled due to adjusting the pH value and adjusting the added concentration of the acidic compound.

[0013] In the present invention, hyaluronic acid is widely distributed in the cell-matrix in the connective tissue, to form a solution with viscosity and elasticity under physiological conditions, and is known to have physical protection to the tissues, vascular endothelial cells and epithelial cells such as iris and retina and provide the main component of the extracellular matrix of buffering effect. In the present invention, hyaluronic acid is not subject to the restriction of physical properties, shape, size, etc., and preferably through sterilization. In addition, hyaluronic acid can have a mean molecular weight of 5-5000kDa, preferably has a mean molecular weight of 5-3000kDa. In addition, hyaluronic acid can be used in the form of pharmaceutically acceptable salts, wherein the pharmaceutically acceptable salts include sodium salts, potassium salts, calcium salts, etc., preferably sodium salts. Further, hyaluronic acid derivatives can also be used, and these derivatives can be particularly combined with chemically modified hyaluronic acid by cross-linking, sulfidation, esterification or amino acid.

[0014] In the present invention, the pH value of the hyaluronic acid aqueous solution may be 1-6, more preferably 1-5, further preferably 1-4, and most preferably 1.5-3.5.

[0015] In the method for preparing hyaluronic acid nanoparticles provided by the present invention, the concentration of the hyaluronic acid aqueous solution can be 0.05-7% (w / v), preferably 0.1-5% (w / v).

[0016] The aqueous solution does not contain a cross-linking agent and an organic solvent.

[0017] After electron beam irradiation, dialysis and freeze-drying steps are further included.

[0018] The size of the hyaluronic acid nanoparticles was controlled by changing the irradiation dose of the electron beam, and the size of the hyaluronic acid nanoparticles was reduced by increasing the irradiation dose of the electron beam.

[0019] In the method for preparing hyaluronic acid nanoparticles provided by the present invention, the electron beam may be irradiated at a dose of 0.5-300 kGy, preferably 1-250 kGy, and most preferably 1-200 kGy.

[0020] In the present invention, the total irradiation energy intensity of the electron beam may be 0.1 MeV to 5 MeV, preferably 0.5 MeV to 3 MeV, and most preferably 1.0 MeV to 2.5 MeV.

[0021] The size of the hyaluronic acid nanoparticles was controlled by adjusting the pH value of the aqueous solution, and increased by decreasing the pH value of the aqueous solution.

[0022] The method for preparing hyaluronic acid nanoparticles provided by the present invention can be a method for preparing hyaluronic acid nanoparticles with a diameter of 100 nm or less, preferably hyaluronic acid nanoparticles with a diameter of 50 nm or less, and most preferably hyaluronic acid nanoparticles with a diameter of 30 nm or less.

[0023] In another aspect, the present invention provides intermolecular or intramolecular cross-linked nanoparticles of hyaluronic acid prepared by the method.

[0024] The nanoparticles are characterized as hydrogels with swelling properties.

[0025] The nanoparticles are characterized by being tumor-selective. Specifically, the nanoparticles are characterized by being colon cancer or melanoma-selective.

[0026] For colon cancer tumors, the nanoparticles were characterized by an 8-fold higher tumor-to-muscle ratio and a 1.5-fold higher tumor-to-blood ratio. For melanoma, the nanoparticles were characterized by a 14-fold higher tumor-to-muscle ratio and a 3-fold higher tumor-to-blood ratio.

[0027] On the other hand, the present invention provides a contrast agent comprising hyaluronic acid nanoparticles labeled with at least one labeling material selected from radioactive isotopes, organic fluorescent materials, quantum dots as inorganic materials, magnetic resonance image contrast agents, computed tomography contrast agents, positron emission tomography contrast agents, ultrasound contrast agents, fluorescent contrast agents and shape shift materials.

[0028] The present invention includes a ligand compound conjugated to the nanoparticle and a radioactive isotope coordinated with the ligand compound.

[0029] The ligand compound is characterized by at least one of NODA-GA-NH2, DOTA-GA, DOTA, TETA and NOTA.

[0030] The radioisotope is characterized by 11 C. 13 N. 15 O. 18 F. 38 K. 62 Cu, 64 Cu, 68 Ga, 82 Rb, 124 I. 89 Zr, 99m Tc, 123 I. 111 In, 67 Ga, 177 Lu, 201 Tl, 117m Sn, 125 I. 131 I. 166 Ho, 188 Re, 67 Cu, 89 Sr. 90 Y. 225 Ac, 213 Bihe 211 At least one of At.

[0031] In another aspect, the present invention provides a conjugate of ascorbic acid and hyaluronic acid nanogel.

[0032] In the present invention, "conjugate" refers to a compound having two or more compounds connected to each other. The connection can be achieved by non-covalent bonds or covalent bonds. That is, the conjugate of the present invention refers to ascorbic acid and hyaluronic acid being directly or indirectly connected to each other by non-covalent bonds or covalent bonds. Preferably, the conjugate of the present invention may refer to the hydroxyl group of ascorbic acid forming a bond with the carboxyl group of hyaluronic acid through a C1 to C5 alkyl group to be firmly connected by a covalent bond.

[0033] In the present invention, "ascorbic acid" is a substance having an antioxidant effect represented by the following chemical formula 1, called vitamin C, which is a water-soluble vitamin and has been used in various industrial applications, including pharmaceutical preparations, feeds, inhibition of melanin accumulation, medicines and cosmetics. However, ascorbic acid is a very unstable compound, and when exposed to heat, air and light during the preparation process, it is unstable under oxidative conditions and thermal conditions and loses its activity, and loses its activity during the distribution process, so its application is greatly limited.

[0034] <Chemical Formula 1>

[0035]

[0036] In the present invention, unless otherwise specified, the term "hyaluronic acid nanogel" refers to all variants of hyaluronic acid, hyaluronate or hyaluronic acid (hyaluronan) with various chain lengths and charge states and various chemical modifications (including cross-linking), and hydrogels having nanometer size by cross-linking the variants. That is, the hyaluronic acid nanogel generally includes nanogels derived from various hyaluronates of hyaluronic acid (such as sodium hyaluronate) with various counterions. For example, the term generally includes hyaluronic acid nanogels derived from various derivatives, such as oxidation, such as oxidation of -CH2OH groups to -CHO and / or -COOH; periodate oxidation of adjacent hydroxyl groups, which selectively involves reduction (e.g., reduction to form an imine by reducing -CHO to -CH2OH), and involves reduction to an amine; sulfidation; selective deamidation or deamidation involving the formation of an amide with a new acid; esterification; cross-linking; substitution with various compounds, which is achieved by conjugation with the aid of cross-linking agents or carbodiimides, including conjugation of hyaluronic acid to various molecules such as proteins, peptides and pharmaceutical active ingredients; and deacetylation.

[0037] In the present invention, the preparation method of the hyaluronic acid nanogel is not particularly limited, as long as the nanogel is a nanoscale hydrogel formed with hyaluronic acid molecules as basic units. In the art, the method for preparing nanoscale hyaluronic acid hydrogel is well known, for example, the preparation method using a cross-linking agent, the preparation method using an electron beam, etc. can be mentioned, but most preferably, the hyaluronic acid nanogel can be prepared by irradiating the above-mentioned hyaluronic acid aqueous solution with an electron beam.

[0038] In the present invention, the conjugate of ascorbic acid and hyaluronic acid nanogel can be represented by the following Chemical Formula 2.

[0039] <Chemical Formula 2>

[0040]

[0041] Here, m is 1 to 5.

[0042] In the conjugate provided by the present invention, the ratio of ascorbic acid molecules to the carboxylic acid groups of hyaluronic acid molecules can be 1-5:1, preferably 1-4:1, more preferably 2-4:1, and most preferably 2-3:1.

[0043] In the present invention, the conjugate of ascorbic acid and hyaluronic acid nanogel can be prepared in sequence according to the following reaction formulas 1 to 3.

[0044] <Reaction formula 1>

[0045]

[0046] <Reaction 2>

[0047]

[0048] <Reaction 3>

[0049]

[0050] Here, m is 1 to 5.

[0051] In reaction formulas 2 and 3 of the present invention, hyaluronic acid can be induced to form a nanogel by cross-linking after the reaction of reaction formulas 2 and 3, and reaction formulas 2 and 3 can also be applied after hyaluronic acid in the form of a nanogel is prepared according to a known method or the method for preparing a hyaluronic acid nanogel provided by the present invention.

[0052] Preferably, in Reaction Formulas 2 and 3 of the present invention, after preparing hyaluronic acid in the form of nanogel according to a known method or the method for preparing hyaluronic acid nanogel provided by the present invention, Reaction Formulas 2 and 3 can be applied.

[0053] According to one embodiment of the present invention, it is confirmed that the ascorbic acid contained in the conjugate has significantly improved stability, and even after the ascorbic acid is placed under very harsh conditions, the ascorbic acid still exhibits physiological activity. Therefore, the conjugate provided by the present invention is characterized in that the storage stability of ascorbic acid is improved.

[0054] In another aspect, the present invention provides a cosmetic composition for anti-oxidation, skin whitening, wrinkle improvement or skin anti-aging, comprising ascorbic acid and hyaluronic acid nanogel as active ingredients.

[0055] Furthermore, the present invention provides a cosmetic composition for anti-oxidation, skin whitening, wrinkle improvement or skin anti-aging, which consists (essentially) of ascorbic acid and hyaluronic acid nanogel as active ingredients.

[0056] The ingredients contained in the cosmetic composition of the present invention include, in addition to the active ingredient, ingredients generally used as active ingredients in cosmetic compositions, for example, general adjuvants such as antioxidants, stabilizers, solubilizers, vitamins, pigments and fragrances, and carriers.

[0057] The cosmetic composition of the present invention can even be prepared in any form of preparation commonly prepared in the art, and can be formulated as, for example, a solution, a suspension, an emulsion, a paste, a gel, an ointment, a lotion, a powder, a soap, a surfactant-containing cleanser, an oil, a foundation, an emulsion foundation, a wax foundation, a spray, etc., but is not limited thereto. More specifically, the cosmetic composition of the present invention can be prepared as a softener (skin), a nourishing toner (milk lotion), a nourishing cream, a massage cream, an essence, an eye cream, a cleansing cream, a cleansing foam, a cleansing water, a mask, a spray or a powder preparation.

[0058] Preferably, the cosmetic composition of the present invention may be a water-in-oil cream, an oil-in-water cream, an oil-in-water essence, and a hydrogel preparation, and most preferably a hydrogel preparation, but not limited thereto.

[0059] When the preparation of the present invention is a paste, cream or gel, animal oil, vegetable oil, wax, paraffin, starch, tragacanth gum, cellulose derivatives, polyethylene glycol, silicone, bentonite, silicon dioxide, talc, zinc oxide and the like can be used as carrier components.

[0060] When the preparation of the present invention is a powder or spray, it may contain lactose, talc, silicon dioxide, aluminum hydroxide, calcium silicate or polyamide powder as a carrier component, especially in the case of a spray, and further includes a propellant such as chlorofluorocarbons, propane / butane or dimethyl ether.

[0061] When the preparation of the present invention is a solution or emulsion, a solvent, a solubilizing agent or an emulsifier can be used as a carrier component. For example, the carrier component includes water, ethanol, isopropanol, ethyl carbonate, ethyl acetate, benzyl alcohol, benzyl benzoate, propylene glycol, 1,3-butylene glycol oil, glycerol fatty esters, polyethylene glycol or fatty acid esters of sorbitan.

[0062] When the preparation of the present invention is a suspension, a liquid diluent such as water, ethanol or propylene glycol, a suspending agent such as ethoxylated isostearyl alcohol, polyoxyethylene sorbitan ester, polyoxyethylene sorbitan ester, microcrystalline cellulose, aluminum metahydroxide, bentonite, agar, tragacanth gum, etc. can be used as a carrier component.

[0063] When the preparation of the present invention is a surfactant-containing cleanser, fatty alcohol sulfates, fatty alcohol ether sulfates, sulfosuccinic acid monoesters, isethionates, imidazolinium derivatives, methyl taurine, sarcosinates, fatty acid amide ether sulfates, alkylamido betaines, fatty alcohols, fatty acid glycerides, fatty acid diethanolamides, vegetable oils, lanolin derivatives, ethoxylated glyceryl fatty acid esters, etc. can be used as carrier components.

[0064] In the present invention, the composition may have antioxidant activity. Antioxidation refers to an effect of inhibiting oxidation. In the human body, pro-oxidants and antioxidants are in a balanced state, but when this balance is imbalanced due to various factors and tends to promote oxidation, oxidative stress is induced, leading to potential cell damage and pathological diseases.

[0065] In one embodiment of the present invention, it is confirmed that the composition exhibits excellent DPPH radical scavenging activity.

[0066] The term "whitening" as used herein refers to whitening the skin, and refers to all effects of inhibiting or preventing melanin skin pigmentation by inhibiting the synthesis of melanin. In the present invention, the composition can inhibit the activity of tyrosinase. Tyrosinase is a metal-containing protein that contains a pair of copper ions at the active site, and tyrosinase is an enzyme involved in the following process: wherein in the melanin production pathway, L-tyrosine is converted into 3,4-dihydroxyphenylalanine (L-DOPA) by hydroxylation reaction, oxidized again to phenylalanine-3,4-quinone (phenylalanine-3,4-quinone) (dapaquinone), and then synthesized into melanin by various intermediates such as dopachrome, indole-5,6-quinone (indole-5,6-quinone).

[0067] In one embodiment of the present invention, it was confirmed that the composition had tyrosinase inhibitory activity in a concentration-dependent manner, and thus it could be seen that the composition had whitening activity.

[0068] In the present invention, the composition may be characterized by inhibiting the production of melanin. Melanin is composed of dark brown granular pigments and is produced by organelles called melanosomes in melanocytes. Melanin is present in the skin, hair, eyes, etc., and the skin color is determined by the amount of melanin. The more melanin, the darker the skin color.

[0069] In one embodiment of the present invention, it was confirmed that the composition had a melanin production inhibitory effect in a concentration-dependent manner, and thus it was seen that the composition had a whitening activity.

[0070] The term "wrinkles" as used herein refers to fine lines produced by skin due to decline, which may be caused by genetic factors, a decrease in collagen present in the dermis of the skin, external environment, etc. In the present invention, the composition may be characterized by promoting the biosynthesis of collagen. Collagen is present in connective tissues such as bones, cartilage, skin and tendons. When the skin is continuously exposed to external stimuli such as ultraviolet rays, the collagen fibers involved in the elasticity of the skin are destroyed, resulting in skin aging.

[0071] In one embodiment of the present invention, it was found that the composition can exhibit wrinkle improvement effects by increasing collagen biosynthesis in a concentration-dependent manner.

[0072] The term "skin aging" used herein shows symptoms such as decreased skin elasticity, decreased radiance, wrinkle generation, decreased regeneration, or severe dryness, and may be due to the passage of time, external environment, and the like.

[0073] In one embodiment of the present invention, it was found that the composition can promote the proliferation of fibroblasts to improve the regeneration and elasticity of damaged skin.

[0074] In another aspect, the present invention provides a food composition for anti-oxidation, skin whitening, wrinkle improvement or skin anti-aging, comprising a conjugate of ascorbic acid and hyaluronic acid nanogel as active ingredients.

[0075] Furthermore, the present invention provides a food composition for anti-oxidation, skin whitening, wrinkle improvement or skin anti-aging, which consists (substantially) of a conjugate of ascorbic acid and hyaluronic acid nanogel as active ingredients.

[0076] The food composition of the present invention includes all forms, such as functional food, nutritional supplement, health food and food additive. Its type can be prepared in various forms according to general methods known in the art.

[0077] For example, as health food, food composition of the present invention itself can be made into tea, fruit juice and beverage form to drink, or taken by granule, capsule and powder form.In addition, food composition of the present invention can be prepared with known materials or active ingredients mixed with known anti-oxidation, skin whitening, wrinkle improvement or skin anti-aging effects.

[0078] In addition, functional foods can be prepared by adding the food composition of the present invention to beverages (including alcoholic beverages), fruits and processed foods thereof (e.g., canned fruits, bottled foods, jams, marmalades, etc.), fish, meat and processed foods thereof (e.g., ham, sausages, corned beef, etc.), bread and noodles (e.g., udon noodles, soba noodles, ramen noodles, pasta, macaroni, etc.), fruit juices, various beverages, biscuits, candies, dairy products (e.g., butter, cheese, etc.), edible vegetable oils, margarine, vegetable proteins, retort foods, frozen foods, various condiments (e.g., soybean paste, soy sauce, dressings, etc.).

[0079] The preferred content of the food composition of the present invention is not limited thereto, but is preferably 0.01 to 50wt% of the total weight of the final prepared food. In order to use the food composition of the present invention in the form of a food additive, the food composition can be used in the form of a powder or a concentrate.

[0080] Furthermore, the present invention also provides the use of a conjugate of ascorbic acid and hyaluronic acid nanogel in the preparation of a medicament for anti-oxidation, skin whitening, wrinkle improvement or skin anti-aging.

[0081] In addition, the present invention provides a method for anti-oxidation, skin whitening, wrinkle improvement or skin anti-aging, which comprises administering an effective dose of a composition comprising a conjugate of ascorbic acid and hyaluronic acid nanogel as active ingredients to an individual in need thereof.

[0082] The term "effective dose" used in the present invention refers to an amount that, when applied to an individual, shows improvement, treatment, prevention, detection and diagnosis of diseases related to anti-oxidation, skin whitening, wrinkle improvement or skin anti-aging, or inhibition or alleviation of diseases related to anti-oxidation, skin whitening, wrinkle improvement or skin anti-aging. The "individual" may be an animal, preferably a mammal, especially an animal including a human, or a cell, tissue or organ derived from an animal. The individual may be a patient in need of such an effect.

[0083] The term "treatment" used in the present invention generally refers to improving diseases related to anti-oxidation, skin whitening, wrinkle improvement or skin anti-aging, or symptoms of diseases related to anti-oxidation, skin whitening, wrinkle improvement or skin anti-aging. The treatment may include treating or substantially preventing these diseases, or improving their symptoms, and includes alleviating, treating or preventing symptoms or most symptoms derived from the disease, but is not limited thereto.

[0084] In the present invention, the term "comprising" is used in the same manner as "containing" or "characterized by", and does not exclude other components or method steps not mentioned in the composition or method. Unless otherwise specified, the term "consisting of..." is used in the same manner as "comprising", and means excluding other elements, steps or ingredients, etc. The term "consisting essentially of..." or "essentially comprising" means that in addition to the components or steps described within the scope of the composition or method, it also includes components or steps that do not affect its basic properties.

[0085] Beneficial Effects

[0086] According to the present invention, a method for preparing pure hyaluronic acid nanoparticles in aqueous solution without using a cross-linking agent and an organic solvent is provided. According to the present invention, by reproducibly and uniformly synthesizing hyaluronic acid nanoparticles of various nanometer sizes under an optimized electron beam, the use of the synthesized hyaluronic acid nanoparticles as a contrast agent and therapeutic agent for tumor diagnosis through skin permeability is provided, and the skin permeability is confirmed by fluorescent labeling and radioactive labeling.

[0087] Description of the drawings

[0088] Figure 1 is a schematic diagram illustrating the formation of hyaluronic acid particles by cross-linking hyaluronic acid polymers with electron beams.

[0089] Figure 2 and Figure 3 This is a graph showing the particle size distribution of hyaluronic acid in Example 1 of the present invention.

[0090] Figure 4 Illustrated is a histogram of the particle size of nanogels according to the irradiation dose of the electron beam when a 0.5% (W / V) aqueous solution (pH 2.0 to 2.4) of hyaluronic acid (HA3) was irradiated with an electron beam up to 100 kDa.

[0091] Figure 5 This is the DLS measurement result of a hyaluronic acid nanoparticle in the sample of Example 1 of the present invention.

[0092] Figure 6 is a photograph of a sample in powder form obtained after mass synthesis of hyaluronic acid nanoparticles and freeze drying.

[0093] Figure 7 is a TEM image of hyaluronic acid nanoparticles prepared according to Example 1 of the present invention.

[0094] Figure 8 is a photograph showing the experimental results of the hydrogel properties of hyaluronic acid nanoparticles prepared according to Example 1 of the present invention.

[0095] Fig. 9Schematic diagram illustrating the process of preparing a chelated compound by conjugating a bifunctional chelate NODA-GA-NH2 into the hyaluronic acid nanoparticles of Example 2 of the present invention.

[0096] Fig.10 Schematic diagram illustrating the process of radiolabeling the hyaluronic acid nanoparticles of Example 2 of the present invention with Cu-64.

[0097] Fig.11 This is a graph illustrating the radiochemical purity results of hyaluronic acid nanoparticles radiolabeled with Cu-64 according to Example 2 of the present invention.

[0098] Fig.12 The results of time-dependent radioactive thin layer chromatography (Radio-TLC) were used to analyze the stability of hyaluronic acid nanoparticles radiolabeled with Cu-64 in Example 2 of the present invention in phosphate buffered saline (PBS) and fetal bovine serum (FBS).

[0099] Fig.13 The results of the in vivo distribution verification experiment of hyaluronic acid nanoparticles radiolabeled with Cu-64 in normal mice according to Example 2 of the present invention are illustrated.

[0100] Fig.14 The results of an in vivo distribution verification experiment are as follows: hyaluronic acid nanoparticles obtained by precipitation with an organic solvent as a final sample, which is different from the freeze-drying process generally used to obtain synthesized hyaluronic acid nanoparticles.

[0101] Fig.15 These are the results of an in vivo distribution verification experiment using the hyaluronic acid nanoparticles of Example 2 of the present invention in a tumor model of colon tumor cells (CT26).

[0102] Fig.16 These are the results of an in vivo distribution verification experiment using the hyaluronic acid nanoparticles of Example 2 of the present invention in a skin cancer cell (melanoma / B16F10) tumor model.

[0103] Fig.17 is a nuclear medicine image of a tumor model using hyaluronic acid nanoparticles labeled with the radioactive isotope Cu-64.

[0104] Fig.18 is a diagram illustrating a process of synthesizing an ascorbic acid derivative by combining 1-chloro-3-iodopropane in the 3-OH group of ascorbic acid protected in the form of acetal, substituting a chloro group (Cl) with an iodine group (I), and removing the acetal group as a protecting group.

[0105] Fig.19 is a diagram illustrating the process of replacing the carboxyl groups of hyaluronic acid nanogels with tetrabutylammonium (TBA) groups.

[0106] Fig. 20 is a diagram illustrating a process of synthesizing a hyaluronic acid nanogel derivative combined with ascorbic acid in a powder form by stirring an ascorbic acid derivative substituted with an iodine group and a hyaluronic acid nanogel obtained in the form of TBA in a DMSO solvent for about 12 hours and adding acetone to the reaction solution.

[0107] Fig.21A and 21B By NMR ( Fig.21A ) and HPLC chromatogram ( Fig.21B ) is a schematic diagram showing whether a hyaluronic acid nanogel derivative combined with ascorbic acid was prepared.

[0108] Fig. 22 The results of evaluating the stability by analyzing the hyaluronic acid nanogel derivative (HA-VitC combined with ascorbic acid) and an ascorbic acid (AA) aqueous solution respectively after standing at 50° C. for 48 hours using HPLC are illustrated.

[0109] Fig.23A and 23B The results of evaluating the ability of each test substance to inhibit melanin production and the ability to inhibit tyrosinase activity are illustrated.

[0110] Fig.24A and 24B is an example of DPPH analysis ( Fig. 24B ) The results of evaluating the free radical scavenging ability of each test substance and quantifying the results by graphs ( Fig. 24B ) icon.

[0111] Fig.25A and 25B It is the result of evaluating the tyrosinase inhibitory ability of each test substance.

[0112] Fig.26 The results of evaluating the ability of each test substance to promote fibroblast proliferation are illustrated.

[0113] Fig. 27 The results of evaluating the effect of each test substance on collagen biosynthesis are illustrated.

[0114] Embodiments of the invention

[0115] Embodiments of the present invention will be described below with reference to the accompanying drawings. The present invention may be modified in various ways and may have various forms, and specific embodiments are illustrated in the accompanying drawings and described in detail in this specification. However, this is not to limit the present invention to specific embodiments, and it should be understood that the present invention covers all modifications, equivalents and substitutes within the concept and technical scope of the present invention. When describing each figure, similar numbers are used for similar components.

[0116] The terms used in this application are only used to describe specific embodiments and are not intended to limit the present invention. Unless otherwise clearly indicated in the context, the singular form may include the plural form. In this application, it should be understood that the term "including" or "having" refers to the presence of the features, numbers, steps, operations, components, parts or combinations thereof described in this specification, but does not exclude the possibility of pre-existing or adding one or more other features, numbers, steps, operations, components, parts or combinations thereof.

[0117] Unless otherwise defined to the contrary, all terms (including technical or scientific terms) used herein have the same meaning as commonly understood by those of ordinary skill in the art. Terms defined in general dictionaries should be understood to have the same meaning as in the relevant technical field, and should not be understood as ideal or overly formal meanings unless explicitly defined in this application.

[0118] Example 1: Analysis of Nanoparticle Synthesis Based on Molecular Weight of Hyaluronic Acid, Electron Beam Conditions and Acid Concentration

[0119] In the case of the electron beam irradiation experiment using hyaluronic acid, the following three kinds of hyaluronic acids having different molecular weights were used and the experiment was conducted under acidic aqueous solution conditions.

[0120] Table 1

[0121] HA1 Oligomeric hyaluronic acid (8kDa) HA2 High molecular weight sodium hyaluronate (2.5MDa) HA3 Low molecular weight sodium hyaluronate (100kDa)

[0122] For reference, through previous studies (Korean Patent Registration No. 1893549), the present inventors confirmed that when 50 kGy of electron beams were irradiated to a 10 kDa 1% (w / v) hyaluronic acid aqueous solution, a 380 nm nanogel was generated, and when 200 kGy of electron beams were irradiated to a 5% (w / v) hyaluronic acid aqueous solution, a 108 nm nanogel was generated. However, under other conditions, no nanogel was formed, and even in the case of nanoparticles prepared under the conditions, it was found that the industrial application was limited due to the large size of the nanoparticles.

[0123] Therefore, the present inventors attempted a method of irradiating an aqueous hyaluronic acid solution with an electron beam under acidic conditions to provide a nanogel having an extremely small particle size and capable of being prepared at an economical cost under conditions of a lower concentration of an aqueous hyaluronic acid solution while using a hyaluronic acid (HA1) of a similar molecular weight (8 kDa) as in previous studies.

[0124] Specifically, HClO4 was added to the HA1 aqueous solution having the concentration (w / v%) shown in Table 2 below to adjust the pH value to pH 1.6-2.1, and then irradiated with an electron beam at an energy of 1 MeV and an irradiation dose (kGy) as shown in Table 2 below.

[0125] The results are shown in Table 2 below.

[0126] As shown in Table 2 below, conditions were confirmed under which small nanoparticles with a particle size of 3-4 nm and a low polydispersity index could be synthesized when different concentrations of hyaluronic acid (HA1) were used and additional acid was added at different electron beam irradiation energies.

[0127] Table 2

[0128]

[0129] Next, in the case of HA2, it was confirmed that when acid A (HClO4) was added to lower the pH to 1.8 to 2.2 and electron beams were irradiated, nanoparticles were well generated, and it was confirmed that the size of the particles tended to increase as the concentration of the added acid increased.

[0130] Table 3

[0131]

[0132] Next, even in the experiment using HA3, it was confirmed that nanoparticles were generated when acid was added. The results are shown in Figure 4 It was further confirmed that the size of the particles tended to increase as the concentration of the added acid gradually increased, and that the size of the particles tended to decrease as the electron beam irradiation dose increased.

[0133] like Figure 5 As shown, it was confirmed by DLS that one particle of the sample synthesized in Example 1 had a size of 8.1 nm.

[0134] like Figure 6 As shown in the photograph, hyaluronic acid nanoparticles showing this result were synthesized in large quantities and obtained as powder samples after freeze-drying.

[0135] In the following experiments, nanoparticles were prepared and used by irradiating a 1% (w / v) HA3 aqueous solution at pH 2.0 with 100 kGy electron beam (irradiation energy of 2.5 MeV).

[0136] (1) Structural analysis of nanoparticles

[0137] The synthesized HA nanoparticles were investigated not only to measure the size of the nanoparticles by DLS but also to directly confirm the morphological shape of the actual synthesized nanoparticles by transmission electron microscopy (TEM).

[0138] 2 to 3 drops of nanoparticles were added to the carbon-coated copper grid, and the staining process was performed using uranyl acetate, and then the nanoparticles were used after sufficient time to fully dry the water. Figure 7 TEM analysis was performed as shown.

[0139] As with the result of DLS, it was confirmed that the nanoparticles had a small size of about 10 nm or less, and it was confirmed that the shape of the particles was unclear but maintained a roughly circular shape.

[0140] (2) Analysis of hydrogel properties

[0141] An experiment was conducted to confirm whether the synthesized nanoparticles had the basic swelling property of the hydrogel, and experiments were performed using pure water and hyaluronic acid without irradiation with electron beams as controls.

[0142] Equal amounts of HA nanoparticles and controls were dissolved in 500 μL of water, respectively, and then centrifuged using a centrifugal filter with a separation membrane to check the amount of water dripping at the bottom of each tube. In order to fully see the difference, the water dripping at the bottom of the tube was dyed with green ink and then captured. Figure 8 shown.

[0143] When the results were confirmed, it was confirmed that in the nanoparticle sample obtained by irradiating an electron beam, the amount of water dripping to the bottom of the tube after centrifugation was less, and more solution remained in the supernatant portion. Through this result, it was confirmed that the hyaluronic acid nanoparticles synthesized by electron beam irradiation swelled further than the control and had characteristics as a hydrogel.

[0144] Example 2: Application of hyaluronic acid nanogel

[0145] (1) Stability evaluation of hyaluronic acid nanogels conjugated with contrast agents

[0146] like Fig. 9As shown in the schematic diagram, the experiment of conjugating hyaluronic acid nanogels was carried out by using NODA-GA-NH2, and the hyaluronic acid nanogels were dissolved in pyridine, and then p-toluenesulfonyl chloride was slowly added dropwise, and the reaction was carried out overnight. After that, after adding NODA-GA-NH2, the reaction was heated and carried out for about 1 day, and then the hyaluronic acid nanogels conjugated with NODA-GA-NH2 were separated by a centrifugal filter. The hyaluronic acid nanogels conjugated with NODA-GA were obtained in the form of pure white powder by freeze drying.

[0147] like Fig.10 As shown in the schematic diagram, Cu-64 was used for radiolabeling, and NODA-GA-hyaluronic acid nanogels were added to a pH 6.8 buffer to react with the hyaluronic acid nanogels at an appropriate temperature and time. 64 After the CuCl2 reaction, the hyaluronic acid nanogel labeled with Cu-64 was purified by centrifugal filter, and the radiochemical purity was confirmed by using Radio-TLC.

[0148] Results, such as Fig.11 As confirmed, the radiochemical purity was very high, almost 100%, and an excellent labeling reaction with Cu-64 was performed.

[0149] In case of the stability of radiolabeled nanoparticles, experiments were performed by detecting radiolysis and the stability of nanoparticles was confirmed by time-dependent Radio-TLC analysis using phosphate buffered saline (PBS) and fetal bovine serum (FBS).

[0150] Results, such as Fig.12 As shown, high stability was confirmed up to 1 hour and 4 hours, and even the result for 24 hours showed excellent stability of 95% or more, so it is expected that stability can be sufficiently maintained even in mice.

[0151] (2) In vivo distribution verification experiment in normal mice

[0152] The in vivo distribution verification experiment was carried out on normal mice using Cu-64 labeled hyaluronic acid (HA) nanogels, and the organ distribution and in vitro release pathways were verified.

[0153] Thereafter, since the synthesized nanoparticles will be used in the development and research of nanogel-based tumor contrast agents, it is planned to conduct experiments at a time when the nanogel can fully target the tumor, therefore, the nanogel is injected and then the experiment is conducted by verifying the distribution in each organ after 24 hours.

[0154] When confirming the results, such as Fig.13As shown, in the case of the synthetic HA nanogel, the highest uptake was shown in the liver.

[0155] Thereafter, during the synthesis of HA nanogels using electron beams, a specific acid (HClO4) was added to the electron beam-irradiated samples to change the pH value, and then an in vivo distribution verification experiment was performed in normal mice ( Fig.14 ), which confirmed that the residual level in the body tended to be significantly reduced overall compared with the above results.

[0156] In addition, even for HA nanogels obtained by a method using organic solvent precipitation, which is different from the freeze-drying process that is usually used to obtain synthetic HA nanogels as final samples, in vivo distribution verification experiments were performed, such as Fig.14 As demonstrated by the results of the present study, the uptake levels of other organs were similar to each other.

[0157] Nanoparticles produced by the Cu-64 labeling reaction were used to conduct an in vivo distribution verification experiment in a tumor model. 24 hours after injection, the distribution in various organs was confirmed and the tumor uptake was confirmed.

[0158] First, when a tumor model was prepared using colon tumor cells (CT26) and the tumor grew to an appropriate size of 6-8 mm, an in vivo distribution verification experiment was performed in this tumor model. Fig.15 It was confirmed that the liver showed the highest uptake of 4.5%ID / g, followed by kidney (1.6%ID / g) and spleen (1.2%ID / g). However, even in tumors, the uptake of 1.0%ID / g showed a high uptake compared with other organs, and the tumor-muscle ratio was 8.4 times and the tumor-blood ratio was 1.9 times, which can be well diagnosed as tumors.

[0159] In addition, a tumor model was prepared using skin cancer cells (melanoma / B16f10), and an in vivo distribution verification experiment was performed 24 hours after the tumor grew to an appropriate size. Fig.16 It was confirmed that the liver, kidney and spleen showed high uptake, but it was confirmed that the nanogel was released in vitro through the liver and kidney, and the tendency of release through the kidney rather than the liver was higher, and it was confirmed that due to the characteristics of the nanoparticles, a high uptake was shown even in the spleen. Next, in the tumor (0.62% ID / g) and lymph node (0.89% ID / g), it was confirmed that a high uptake was shown, and the tumor-muscle ratio was 14.2 times, and the tumor-blood ratio was 3.2 times, which can be well diagnosed for tumors.

[0160] Nuclear medicine imaging studies of tumor models using hyaluronic acid nanogels labeled with the radioactive isotope Cu-64 confirmed the detailed organ uptake, organ distribution and release that had not been confirmed in the above-mentioned in vivo distribution validation experiments, and confirmed the ability to target tumors.

[0161] In nuclear medicine imaging experiments, colon tumor cells (CT26) were used. Fig.17 As confirmed, in the 5-hour PET images of the hyaluronic acid nanogel, it can be seen that the highest signal is shown in the liver in the same manner as in the in vivo distribution verification experiment, and then high uptake is confirmed in the order of colon and tumor.

[0162] Example 3: Synthesis of hyaluronic acid nanoparticles combined with vitamin C and evaluation of their efficacy

[0163] (1) Synthesis of hyaluronic acid nanoparticles bound to ascorbic acid

[0164] 1) Synthesis of ascorbic acid derivatives

[0165] As a method for efficiently combining hyaluronic acid and ascorbic acid, a strategy for synthesizing ascorbic acid derivatives by combining with the carboxyl group of hyaluronic acid via an ester bond has been established.

[0166] A method for selectively binding the hydroxyl group at the 3-position of ascorbic acid protected in the form of acetal (1-chloro-3-iodopropane, NaHCO3, DMSO) was found, and the protecting group was removed to synthesize an ascorbic acid derivative capable of binding to hyaluronic acid ( Fig.18 ).

[0167] Specifically, an ascorbic acid derivative ( Fig.18 ).

[0168] (2) Synthesis of hyaluronic acid nanoparticles bound to ascorbic acid

[0169] The prepared ascorbic acid derivative was combined with the hyaluronic acid nanoparticles prepared in Example 1.

[0170] Since the hyaluronic acid nanoparticles with carboxyl groups are not soluble in DMSO as a reaction solvent, a tetrabutylammonium (TBA) group substitution method is used. Specifically, the hyaluronic acid nanoparticles containing carboxyl groups are dissolved in water, TBAOH is gradually added to adjust the pH value to pH = 9 to 10, and then freeze-dried to prepare TBA-form hyaluronic acid nanogels ( Fig.19 ).

[0171] Then, the prepared iodine-substituted ascorbic acid derivative and TBA-form hyaluronic acid nanogel were stirred in a DMSO solvent for about 12 hours, and then acetone was added to the reaction solution, thereby obtaining a powdered hyaluronic acid nanogel derivative combined with ascorbic acid ( Fig. 20 ).

[0172] The NMR and HPLC chromatograms were used to confirm whether the hyaluronic acid nanogel derivatives combined with ascorbic acid were prepared, such as Fig.21A and 21B As shown in FIG21 , a proton peak of ascorbic acid at 4.9 ppm and a CH2 peak of a propyl linker at 2.1 ppm were confirmed, and an ester bond was formed between ascorbic acid and hyaluronic acid ( Fig.21A ), and even a peak corresponding to ascorbic acid was confirmed in the HPLC chromatogram ( Fig.21B ).

[0173] The NMR analysis results confirmed that the ratio of ascorbic acid to the carboxylic acid of the hyaluronic acid molecule was 2.5: 1. In other words, it was confirmed that one ascorbic acid was bonded to every 2.5 carboxyl groups of the hyaluronic acid molecule.

[0174] (2) Stability and efficacy evaluation of hyaluronic acid-ascorbic acid nanoparticles (HA-VitC)

[0175] Ascorbic acid (AA, 100 μM) and the prepared hyaluronic acid-ascorbic acid nanogel (HA-VitC, 0.5 mg / mL) aqueous solutions were placed at 50°C for 48 hours and then analyzed by HPLC for thermal stability evaluation.

[0176] The results are shown in Fig. 22 .

[0177] like Fig. 22 As shown, it was confirmed that ascorbic acid (AA) was not oxidized over time, and HA-VitC was stable (stability was improved by 50% or more) compared with ascorbic acid (AA).

[0178] (3) Evaluation of the whitening, antioxidant and wrinkle improvement effects of hyaluronic acid-ascorbic acid nanoparticles (HA-VitC)

[0179] After each test substance was administered to the B16F10 mouse melanoma cell line and each test substance was incubated for 48 hours, the whitening efficacy evaluation was measured by melanin content determination and cell tyrosinase activity determination. As a control, ascorbic acid, ascorbic acid-2-glucoside (AA2G) and HA1 (Oligo-HA) used in Example 2 were used.

[0180] The substances used in the experiments were placed at -20°C or 50°C for 24 hours before being used in the experiments.

[0181] The results are shown in FIG23 .

[0182] like Fig.23A and 23B As shown, ascorbic acid, AA2G, HA-VitC and oligomeric hyaluronic acid (Oligo-HA) were placed at 50°C for 24 hours, respectively, and then their efficacy was compared with that of the samples stored at -20°C. The results showed that in the case of ascorbic acid, the whitening effect disappeared during storage at 50°C, but in the case of HA-VitC, it was confirmed that melanin production and tyrosinase activity were still strongly inhibited in a concentration-dependent manner.

[0183] Then, the free radical scavenging ability of HA-VitC was evaluated using the DPPH assay. Specifically, ascorbic acid, oligo-HA, and HA-VitC were treated for each concentration shown in FIG. 24. The free radical scavenging ability was then evaluated according to conventional known methods ( Fig.24A ) and are quantified and shown in the figure ( Fig. 24B ).

[0184] refer to Fig.24A and 24B , in the case of hyaluronic acid (Oligo-HA), since it has no free radical scavenging ability, it can be determined that the free radical scavenging ability of HA-VitC is displayed by vitamin C (Vit C) bound to HA nanogel in HA-VitC.

[0185] In particular, considering that vitamin C is very easily oxidized after being exposed to air and then rapidly decomposes, in the case of the HA-VitC of the present invention, it is determined that the utilization rate thereof is very high by improving the storage stability of vitamin C while having the effects of vitamin C.

[0186] Next, the cell tyrosinase inhibitory activity of HA-VitC was evaluated according to known methods:

[0187] Cell line: B16F10 mouse melanoma (passage 10), 6-well plate, 4×10 5 Cells / well

[0188] Evaluation method: Cellular tyrosinase activity assay

[0189] Experimental material processing time: 48 hours

[0190] Experimental substance treatment concentration: see Figure 25

[0191] The result is shown in FIG25 .

[0192] like Fig.25A and25B As shown, it was confirmed that HA-VitC inhibited cellular tyrosinase in a concentration-dependent manner.

[0193] Then, the proliferation effect on fibroblasts was evaluated according to a conventionally known method.

[0194] Briefly, the experimental conditions were as follows, and the types of experimental substances and the treatment concentrations of each substance were as follows Fig.26 As shown:

[0195] Cell line: HDF-neo, primary human dermal fibroblasts-neonatal (passage 15), 24-well plate, 1×10 4 Cells / well

[0196] Evaluation methods: WST-8 assay (Ez-cytox) and Procollagen ELISA (Takara #MK101)

[0197] Experimental substance treatment time: 3 days, 1 day fasting, serum-free state

[0198] The results are shown in Fig.26 .

[0199] like Fig.26 As shown, it was confirmed that ascorbic acid, AA2G (AG), and APPS showed little effect in promoting fibroblast proliferation, but HA-VitC promoted fibroblast proliferation in a concentration-dependent manner.

[0200] Next, the effect of HA-VitC on collagen biosynthesis was evaluated according to conventional known methods. Briefly, the experimental conditions were as follows, the types of experimental substances and the treatment concentrations of each substance were as follows: Fig. 27 As shown:

[0201] Cell line: HDF-neo, human primary dermal fibroblasts-neonatal (passage 11), 96-well plate, 3×10 3 Cells / well

[0202] Evaluation method: Procollagen ELISA (Takara #MK101)

[0203] Experimental substance treatment time: 3 days, 1 day fasting, serum-free state

[0204] The results are shown in Fig. 27 .

[0205] like Fig. 27 As shown, it was confirmed that the highest collagen biosynthesis was induced in the HA-VitC treated group.

[0206] Industrial Applicability

[0207] The present invention provides a method for preparing pure hyaluronic acid nanoparticles in an aqueous solution without using a crosslinking agent and an organic solvent. By reproducibly and uniformly synthesizing hyaluronic acid nanoparticles of various nanometer sizes under optimized electron beam conditions, the present invention can be very useful for developing contrast agents and therapeutic agents for tumor diagnosis using the synthesized hyaluronic acid nanoparticles through skin permeability confirmed by fluorescent labeling and radioactive labeling, and thus the industrial applicability of the present invention is very excellent.

Claims

1. A method for preparing cross-linked hyaluronic acid nanoparticles, comprising: Adjusting the pH value of the hyaluronic acid aqueous solution to control the size of the hyaluronic acid nanoparticles, and The hyaluronic acid aqueous solution is irradiated with an electron beam to form intermolecular or intramolecular cross-linked hyaluronic acid nanoparticles, in, The pH value of the hyaluronic acid aqueous solution is 1 to 4, the hyaluronic acid has an average molecular weight of 5 to 5000 kDa, the concentration of the hyaluronic acid aqueous solution is 0.05% to 7% (w / v), the aqueous solution does not contain a cross-linking agent and an organic solvent, the electron beam is irradiated with an irradiation dose of 0.5-300 kGy, the diameter of the hyaluronic acid nanoparticles is 100 nm or less, and an acid is added to the hyaluronic acid aqueous solution.

2. The method of claim 1, wherein the acid is HClO4.

3. The method of claim 1, wherein the size of the hyaluronic acid nanoparticles is controlled by changing the irradiation dose of the electron beam.

4. The method of claim 1, wherein the size of the hyaluronic acid nanoparticles is reduced by increasing the irradiation dose of the electron beam.

5. Hyaluronic acid nanoparticles prepared according to the method according to any one of claims 1 to 4. The hyaluronic acid nanoparticles of claim 5 , wherein the nanoparticles are tumor selective.

7. A contrast agent composition comprising the hyaluronic acid nanoparticles of claim 5 or 6, wherein the hyaluronic acid nanoparticles are labeled with at least one labeling material selected from the group consisting of radioactive isotopes, organic fluorescent materials, quantum dots as inorganic materials, magnetic resonance image contrast agents, computer tomography contrast agents, positron emission tomography contrast agents, ultrasound contrast agents, fluorescent contrast agents and deformable materials.

8. The contrast agent composition of claim 7, comprising: a ligand compound conjugated to the nanoparticle; and A radioactive isotope coordinated to the ligand compound.

9. The contrast agent composition of claim 8, wherein the ligand compound is at least one of NODA-GANH2, DOTA-GA, DOTA, TETA and NOTA.

10. The contrast agent composition of claim 7, wherein the radioisotope is 11 C. 13 N. 15 O. 18 F. 38 K. 62 Cu, 64 Cu, 68 Ga, 82 Rb, 124 I. 89 Zr, 99m Tc, 123 I. 111 In, 67 Ga, 177 Lu, 201 Tl, 117m Sn, 125 I. 131 I. 166 Ho, 188 Re, 67 Cu, 89 Sr. 90 Y. 225 Ac, 213 Bihe 211 At least one of At.

11. A conjugate of ascorbic acid and hyaluronic acid nanogel, wherein the hyaluronic acid nanogel is prepared according to the method according to any one of claims 1 to 4, The conjugate is represented by the following chemical formula 2: <Chemical Formula 2> Wherein m is 1 to 5.

12. The conjugate of claim 11, wherein the conjugate is prepared by the following reaction formulas 1 to 3: <Reaction formula 1> <Reaction 2> <Reaction 3> Wherein m is 1 to 5.

13. The conjugate of claim 11, wherein the conjugate has improved storage stability of ascorbic acid.

14. A cosmetic composition for anti-oxidation, skin whitening, wrinkle improvement or skin anti-aging, comprising the conjugate according to any one of claims 11 to 13 as an active ingredient.

15. A food composition for anti-oxidation, skin whitening, wrinkle improvement or skin anti-aging, comprising the conjugate according to any one of claims 11 to 13 as an active ingredient.

16. Use of the conjugate according to any one of claims 11 to 13 in the preparation of a medicament for anti-oxidation, skin whitening, wrinkle improvement or skin anti-aging.

17. A non-therapeutic method for antioxidant, skin whitening, wrinkle improvement or skin anti-aging in an individual, the method comprising administering to an individual in need thereof an effective dose of a composition comprising the conjugate of any one of claims 11 to 13 as an active ingredient.

Citation Information

Patent Citations

  • Biocompatible nanoparticle and use thereof

    KR101893549B1

  • Assembly system and device for cartridges for aerosol delivery devices

    KR1020190003966A

  • Biocompatible nanoparticle and use thereof

    US20180327554A1